Characteristics of trigonometric control network marks in the Primorska region - Triglav Čekada, Mihaela (Geodetski vestnik, 2022)
An analysis of the present-day geodetic marks representing trigonometric points of the 2nd and 3rd order was carried out in the area of Slovenia that was part of the Kingdom of Italy between 1920 and 1947. By reviewing topographies, photographs on hribi.net and sample field surveys, we identified, among the 52 2nd order points, 16 points that had the Italian type of geodetic marks and 6 points with even older types of geodetic marks, dating back to the Austro-Hungarian Monarchy. Among the 407 3rd order points, we identified 68 Italian geodetic marks and 15 even older ones. The so-called Italian type of geodetic mark can be recognised as a concrete pillar with a square or octagonal shape, about 1 m high, with a diameter of 40 to 70 cm. The even older geodetic marks are carved from natural stone. These often have the dual function of being a trigonometric point mark and a land cadastral mark, indicating the boundary of cadastral municipalities. We also investigated the eccentric metal target signals erected in 1996, and those between 1995 and 1997, which were an additional postconsolidation of the existing granite trigonometric marks installed after the Second World War. Finally, we highlight the potential of these old geodetic marks in the design and planning of new measurements in the future.
Keywords: geodetic mark; geodetska znamenja; national trigonometric networks; stabilisation; stabilizacija; trigonometric pillar; trigonometric point; trigonometrične mreže; trigonometrične točke